IGF1 Knockdown Hinders Myocardial Development through Energy Metabolism Dysfunction Caused by ROS-Dependent FOXO Activation in the Chicken Heart. (24th December 2019) - Gong, Yafan; Yang, Jie; Liu, Qi; Cai, Jingzeng; Zheng, Yingying; Zhang, Yuan; Yu, Dahai; Liu, Honggui; Zhang, Ziwei
Abstract : Insulin-like growth factor 1 (IGF1) is a multifunctional cellular regulatory factor that can regulate cell growth and development by mediating growth hormone stimulation. However, the mechanism of IGF1 dysfunction in cardiomyocyte development is seldom reported. To study this, we employed the models of IGF1 knockdown in chicken embryo in vivo and in cardiomyocytes in vitro. We detected the antioxidant capacity, PI3K/Akt pathway, energy metabolism-related genes, and myocardial development-related genes. Our results revealed that the low expression of IGF1 can significantly suppress the antioxidant capacity and increase the ROS (P < 0.05 ) levels, activating the AMPK and PI3K pathway by inhibiting the expression of IRS1. We also found that myocardial energy metabolism is blocked through IGF1, GLUT, and IGFBP inhibition, further inducing myocardial developmental disorder by inhibiting Mesp1, GATA, Nkx2.5, and MyoD expression. Altogether, we conclude that low IGF1 expression can hinder myocardial development through the dysfunction of energy metabolism caused by ROS-dependent FOXO activation.